MODERN TREATMENT AND EVACUATION ASPECTS OF THE TRAUMATOLOGICAL ASSISTANCE PROVIDED TO THE WOUNDED WITH THE TIBIAL GUN SHOT INJURIES AT THE LEVEL OF MEDICAL MAINTENANCE - Khomenko, I.P.; Korol, S.O.; Matviychuk, B.V.; Chelishvili, A.L.; Sichinava, R.M. (World of Medicine and Biology, 2019)
The purpose of the work was to analyze the proportion of the gunshot wounds in the structure of the battle surgical trauma, to determine the features of medical and evacuation measures during the anti-terrorist operation / operation of the combined forces in the east of Ukraine. The total mass of the study was 489 wounded who had 805 injuries in the shin from 2014 to 2018. The scale of the assessment of the severity of a military surgical trauma was used. On the basis of the comprehensive study, it was found that injuries of the leg made up 23.95% in the overall structure of limb traumatic trauma. In the wounded with firearms fractures of the shin bones and the teeth of the limbs in the first level of medical care, a temporary stop of the bleeding, an early aseptic dressing, anesthesia, immobilization by means of adjuvant and urgent medical evacuation to the second level of medical care are necessary. At the second level, primary surgical treatment of the wound (91.86%) and fasciotomy (44.19%) are predominantly performed. An important anti-shock measure of the second level is the stable superimposition of the rod body of external fixation (43.02%), as well as the administration of antibiotics and tetanus toxoid. At the third and fourth levels of medical care, the overwhelming majority consisted of repeated surgical wound treatment, fasciotomy, reconstructive-restorative surgical intervention (pα